When the cannons roar, comics panels fall silent: on silent representations of traumatic events in Israeli comics and graphic novels. Issue 5 (20th October 2022) - Adler, Silvia; Kohn, Ayelet
Abstract : The present study examines silent panels in five Israeli graphic novels and comics that deal – directly or indirectly – with traumatic events, whether personal, national, or both. Much has been written about comics and trauma. Such studies have mainly been aimed at revealing the importance of comics in documenting, confronting, witnessing, remembering, and reporting trauma; or answering questions such as how fiction and nonfiction comics and graphic narratives shape the traumatic event, or why the graphic memoir is a powerful instrument for coming to terms with the traumatic experience. Yet, the intersection between silence and trauma in graphic narratives has not received sufficient attention. A quick overview of the works chosen for our analysis illustrates that silence, as a theme, may relate to (a) the genre itself; (b) the authors' individual artistic language and self-reflexivity; and (c) the specific episode of personal or national trauma being dealt with in the work. In this paper, we wish to illuminate the diverse roles silence fulfills in comics dealing with trauma, which we hope will be useful in bolstering the value of silence as a form of expression – not only in oral and written communication, but also in multimodal texts – and thus substantiate current theories on silence as a semiotic sign. Our study is conducted in the framework of silence theories, which claim that silence is a meaningful signifier as long as it serves a purpose and is related to intention. It is also carried out within the framework of multimodal discourse theories. Specifically highlighting the idiosyncrasies of the Israeli arena, the present paper also addresses a significant body of works on the representation of trauma in comics.